Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1111/j.1432-1033.1983.tb07558.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Substrate Specificity Determinants for the H4‐Specific Protease‐Activated Protein Phosphotransferase

Abstract: The specificity of the histone-H4-specific, protease-activated protein kinase (H4-PK) was examined using two series of synthetic peptides corresponding to the phosphorylation sites in histone H4 and pyruvate kinase. Optimum kinetic constants for phosphorylation were observed using the peptide Val-Lys-Arg-Ile-Ser-Gly-Leu. Peptides in which the Lys was replaced by Arg or the Lys-Arg sequence was transposed were phosphorylated with less favorable kinetics. Peptides with either basic residue deleted did not serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Also of note is that the sequence GTES in sequencing rounds 8 -11 does not occur at any other position in MLCK, further strengthening the conclusion that the phosphorylated residue at this phosphorylation site is Ser-439. The sequences at both phosphorylation sites are consistent with the specificity determinants identified in previous studies (27)(28)(29). Phosphorylation of synthetic peptides from the PAK substrates H4 (27), S6 (28), and RLC (10,29) has demonstrated that optimum reactivity is observed with Arg at position P-1 or P-3.…”
Section: Pak2supporting
confidence: 88%
“…Also of note is that the sequence GTES in sequencing rounds 8 -11 does not occur at any other position in MLCK, further strengthening the conclusion that the phosphorylated residue at this phosphorylation site is Ser-439. The sequences at both phosphorylation sites are consistent with the specificity determinants identified in previous studies (27)(28)(29). Phosphorylation of synthetic peptides from the PAK substrates H4 (27), S6 (28), and RLC (10,29) has demonstrated that optimum reactivity is observed with Arg at position P-1 or P-3.…”
Section: Pak2supporting
confidence: 88%
“…15), there is an arginine located two amino acids upstream of this serine. Such a configuration resembles a diagnostic feature of at least two protein kinase target sites (27,28). As appropriate upstream arginines are associated with relatively few of the serines encoded within per ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, site 3 may represent an alternate trypsin cleavage of site 1. Previous studies have demonstrated that the S6/H4 kinase requires a dibasic sequence, preferably K-R, amino-terminal to the modified serine (25). Depending on the enzyme/trypsin ratios and extent of endogenous phosphorylation, site 3 may be generated by trypsin cleavage between the K and R, as opposed to cleavage at the carboxyl side of R for site 1.…”
Section: Discussionmentioning
confidence: 99%